Acute relapse of Multiple Sclerosis (MS) in an adolescent patient after Tuberculin skin test (TST): a case report - Kasra Pirahesh; Aria Motamedi-Jahromi (Neurology Letters, 2022)
Activation of MS as a result of bacterial and viral infections is proposed by various studies. However, immune responses initiated by a bacterial antigen can rarely lead to the activation or occurrence of MS. Hereby, we report a unique case of Multiple Sclerosis (MS) relapse following a Tuberculin skin test (TST). After one year of MS remission, a 13-years old female, presented with symptoms supporting tuberculosis (TB), although TST denied TB infection. Two weeks later, the patient returned with symptoms indicating MS relapse, confirmed by magnetic resonance imaging (MRI). A series of immune system interactions, starting with the activation of Toll-like receptors (TLRs) by Mycobacterial components, may expose the central nervous system (CNS) to autoimmune reactions. TST-induced type IV hypersensitivity can be another parallel mechanism in light of MS being a CD4 T-cell mediated disease. This case report highlights the importance of environmental factors such as bacterial agents in the pathophysiology of MS.